Administration of Autologous Mesenchymal Stem Cell Transplantation for Treatment of Type 1 Diabetes Mellitus - Ensieh NASLI ESFAHANI; Ardeshir GHAVAMZADEH; Nika MOJAHEDYAZDI; SeyyedJafar HASHEMIAN; Kamran ALIMOGHADAM; Narjes AGHEL; Behrouz NIKBIN; Bagher LARIJANI (Tehran University of Medical Sciences, 2015)
Background: The aim of the present clinical trial was to investigate the efficacy of autologous bone marrow mesenchymal stem cells (BM-MSCs) in glycemic control of diabetic patients without using any immunosuppressive drugs over a nine-month period. Method: Twenty-three patients with T1DM, at 5 to 30 years of age and in both sexes, participated in this study. This trial consisted of two phases; in the end of the first phase (three month after the transplantation), if the patient still needed exogenous insulin to control his/her glycemic state, the second phase of study was performed. In both phases, 100 milliliter of mixed mesenchymal stem cells and normal saline containing 2×10⁶ autologous cells/kg for each patient was delivered to patients through cubital vein. All patients were evaluated at 1, 3, 6 and 9 months after the procedure. Result: Twenty-one patients underwent a second injection. Nine patients (39%) responded positively and 14 patients (61%) responded negatively based on their HbA1c levels and insulin requirements in both injections. Two patients became insulin-free during two rounds of injections. In responder patients, mean levels of C-peptide and HbA1c as well as prescribed insulin dosage significantly decreased compared to baseline measures (P=0.002, P=0.007 and P<0.001). In the second phase, responder patients did not show significant reduction in C-peptide levels compared to the baseline of the second phase. Mean levels of HbA1c and prescribed insulin dosage significantly decreased in comparison to the beginning of the study (P<0.05). Conclusion: Transplantation of BM-MSC can be viewed as a promising, simple, safe, and efficient therapeutic modality for T1DM.   Keywords: Hematopoietic stem cell transplantation, Diabetes mellitus type 1,  Autologous